E-Financing and the Quest for Financial Inclusion in Tanzania (Tanzania Journal for Population studies and Development, 2019)
Electronic money transfer (e-finance) has gained support by the government of Tanzania as an innovative payment system that provides financial opportunities to both rural and urban populations. However, despite the fact that e-finance offers many advantages to both public and private institutions and individual clients; and that it has been promoting financial inclusion through the provision of affordable, accessible and relevant financial products to individual as well as firms, yet it is not without challenges. Therefore, this paper sets out to examine current trends in relation to financial inclusion, and issues and challenges associated with electronic money transfers in Tanzania. It focuses on the dynamics of financial inclusion and challenges of electronic money transfers such as security risks, including cybercrimes (theft, spies, hackers, and fraudsters). Also, it delves into how low level of understanding by some clients and service providers is a challenge in e-finance since the two parties share sensitive information through company computers as well as pin codes when transacting electronic money. The paper recommends that it is imperative for the government and other stakeholders to train both clients and service providers on the safe use of e-finance and establish anti-cybercrime control mechanisms.